ĐẶC ĐIỂM NGÔN NGỮ TRẦN THUẬT TRONG TIỂU THUYẾT LỊCH SỬ NGUYỄN DU CỦA NGUYỄN THẾ QUANG - Nguyễn, Thị Thẩm Mỹ (Trường Đại học Đà Lạt, 2023)
In this article, we introduce some basic language characteristics in Nguyễn Du by Nguyen The Quang: Narrative language, dialogue language, and monologue language. We discuss the ideology and theme of the work as well as contribute to affirming the value of the work in the development of the modern Vietnamese novel, especially historical fiction.